2013
DOI: 10.1681/asn.2012060590
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effect of Combined Inhibition of Angiotensin-Converting Enzyme and Histone Deacetylase

Abstract: The Connectivity Map database contains microarray signatures of gene expression derived from approximately 6000 experiments that examined the effects of approximately 1300 single drugs on several human cancer cell lines. We used these data to prioritize pairs of drugs expected to reverse the changes in gene expression observed in the kidneys of a mouse model of HIV-associated nephropathy (Tg26 mice). We predicted that the combination of an angiotensin-converting enzyme (ACE) inhibitor and a histone deacetylase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 39 publications
2
35
0
1
Order By: Relevance
“…Counterintuitive regulation of 2 of these 4 peptides was observed after RASi as RASi amplified the DN-induced changes for Napsin-A or SOX-6 fragments. Similar observations were reported in the past, where RASi was shown to exacerbate disease-induced changes while improving kidney function and histology 34 .…”
Section: Resultssupporting
confidence: 89%
“…Counterintuitive regulation of 2 of these 4 peptides was observed after RASi as RASi amplified the DN-induced changes for Napsin-A or SOX-6 fragments. Similar observations were reported in the past, where RASi was shown to exacerbate disease-induced changes while improving kidney function and histology 34 .…”
Section: Resultssupporting
confidence: 89%
“…Testing of this drug combination in Tg26 mice revealed that the combination of both agents provided additional renal protection compared to treatment with either drug alone, as assessed in terms of the reduction of proteinuria, improvement of renal function and attenuation of kidney injury. 80 Our findings indicate that drug-induced changes in expression signatures can be used for predicting the effects of combination drug therapy.…”
Section: Novel Uses For Systems Biologymentioning
confidence: 77%
“…The apparent deleterious effect of HDAC1 inhibition by GRK4γ 142V may seem to contradict the beneficial effects of systemic HDAC inhibitors on inflammation, asthma (43), pulmonary circulation (44), oncogenesis (45), kidney disease (46), myocardial hypertrophy (47,48), and BP control (28,49). However, Class 1 HDAC inhibition may have deleterious effects on cardiac function (50).…”
Section: Discussionmentioning
confidence: 99%